THE ROLE OF THE STATE IN THE DEVELOPMENT OF THE RUSSIAN ECONOMY: MODERN STAGE - G. Ryazanova; P. Tolkachev (Вестник университета, 2018)
The role of the state in the development of the Russian economy is explored. The thesis is substantiated that the chosen after the collapse of the USSR economic model oriented to market relations has exhausted itself. It was unable to ensure a sustainable industrial development. At the modern stage Russia must make an economic breakthrough to restore the necessary industrial potential, which can be realized only by the national state. In addition, the mobilization of public resources for the accelerated development of the national economy follows from the current difficulties of economic and political relations with Western countries.